The Indonesian Outsourcing Workers' Rights in the Tourism Business Sector - Sudiarawan, Kadek Agus; Dharmawan, Ni Ketut Supasti; Karunian, Alia Yofira; Dananjaya, I Komang; Lokahita, Kadek Indira (Lentera Hukum, 2023)
The problem of outsourcing workers extends to the tourism industry. The unique challenge of 'seasonality' makes it more difficult to protect the outsourcing workers' legal rights in the said sector. The research examines the outsourcing regulation in Indonesia by referring to the Job Creation Law, by questioning whether the existing regulations provide prominent legal protection for outsourcing workers, especially in tourism sectors, and how the future law allows for improved protection. The research method used is normative legal research with statutory and legal conceptual approaches. The results of the study show that the amendment of the Manpower Law incorporated into the Job Creation Law and its implementing legal instruments significantly changed outsourcing regulation. As the Job Creation Law has abolished Article 64 of the Manpower Law, the scheme established by the Constitutional Court to prevent companies from exploiting workers in their decisions has become vague in the Job Creation Law. Following global practices, the country can implement a flexible workers policy while simultaneously protecting their rights which Indonesia must adopt.Keywords: Outsourcing, Rights Protection, Tourism Business.